PENGEMBANGAN E-MARKETING SEBAGAI SISTEM INFORMASI LAYANAN PELANGGAN PADA MEGA FLORIST BANDAR LAMPUNG - Tri Darma Rosmalasari; Mega Ayu Lestari; Fajar Dewantoro; Edwin Russel (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2020)
Mega Florist Bandar Lampung is a company engaged in the field of flower board rental and delivery services in the Bandar Lampung area, Mega Florist itself has been established since April 2015. The purpose of this research is to design an e-marketing system and implement an e-marketing system as a customer service at Mega Florist Bandar Lampung. The problem with Bandar Lampung's Mega Florist itself is that there is no system to market board flower rentals, and its marketing still uses brochures, print media, and advertisements so that it requires more costs to market board flower rental services to Mega Florist Bandar Lampung. The system development method uses the waterfall method and the system design uses the UML system design, and the system implementation uses an object-based programming language that is PHP, with Dreamwever and MySQL applications as a database. The result of this research is an online application based on e-marketing built by Mega Florist Bandar Lampung, focused on spreading information on package rental and flower delivery. This web board will present services, facilities, menus, promos and provide convenience for customers in finding information interest rates offered, as well as services in booking board interest rentals.